Pengaruh Pengeluaran Pemerintah Di Bidang Subsidi, Pendidikan, dan Kesehatan Terhadap Kemiskinan - Martha Carolina (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2022)
The problem of poverty is related to other aspects such as health, education, social, economic, cultural, and other aspects. The expenditure aspect is a crucial aspect for the government because the amount of expenditure is determined directly by the government and can ultimately affect the poverty rate. Based on the above, this study will discuss the impact of government spending on education, health, and subsidies for poverty in Indonesia. The data used in this study is secondary data in the form of an annual period from 1992 to 2020. This study uses a quantitative approach with the regression method. The subsidy variable (X1) has an effect on poverty (Y). As subsidies increase, poverty increases. These results indicate that the subsidy budget provided by the government is less targeted at reducing poverty. Government spending on education (x2) has an effect on poverty (Y). As education expenditure increases, poverty decreases. Government spending in the health sector (X3) has no effect on poverty (Y).